Boreal summer intraseasonal oscillation-related precipitation in eastern China modulated by Pacific sea surface temperature - Liyuan Weng; Ping Liang; Yanluan Lin (Environmental Research: Climate)
The boreal summer intraseasonal oscillation (BSISO) is a key source of subseasonal to seasonal predictability, significantly enhancing precipitation in eastern China when BSISO convection is over the Indian Ocean. While background sea surface temperature (SST) modulates the strength and propagation of BSISO, how the SST further modulates the BSISO-caused precipitation change in eastern China is not well understood. Based on observations and National Center for the Environmental Prediction-National Center for Atmospheric Research reanalysis, this study shows the enhanced rainband caused by BSISO shifts latitudinally on interannual timescale in eastern China. Composite and correlation analyses reveal that this interannual shift is closely associated with the Pacific meridional mode (PMM) in preceding boreal spring (February–April). Specifically, the rainband in eastern China shifts southward during the positive PMM phase and northward during the negative phase. During the positive PMM phase, an upper-level anticyclonic anomaly forms over the North Pacific, which strengthens the BSISO-triggered Rossby wave train and results in a southward shift of the westerly jet in eastern China. The ascent along the southern flank of the westerly jet also shifts southward. Besides, a lower-level cyclonic anomaly forms over the western North Pacific as a Gill-type response to warm SST anomalies in the eastern Pacific. This response weakens the western North Pacific subtropical high and the background easterly wind over the tropical Pacific, impeding the eastward propagation of BSISO. Both the weakened subtropical high and the impeded BSISO favour a southward shift of moisture convergence in eastern China. During the negative PMM phase, the BSISO-triggered Rossby wave train is weakened and the westerly jet and the ascent in eastern China shift northward. The moisture convergence in eastern China also shifts northward due to the strengthened subtropical high and the eastward extension of BSISO. These results can provide guidance for subseasonal forecast of summer precipitation in eastern China.